The aircraft gas turbine engineering and its operation (Pratt and Whitney Aircraft, 1974)
Gas turbine engine fundamentals -- Gas turbine engine terms -- Gas turbine engine components -- Gas turbine engine operation -- Engine operational characteristics -- Gas turbine engine performance.